Kejahatan Bioterorisme Dalam Perspektif Hukum Pidana Indonesia - Hariyanto, Hariyanto (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The crime of bioterrorism is a terror threat that is very dangerous and difficult to detect so that it will have a major impact on the fulfillment of human rights, the regulation of bioterrorism crimes in Indonesia which has not been limited has increased the chances of attacks by biological agents that can occur at any time. The purpose of this research is to analyze the actions that are classified as bioterrorism crimes in the perspective of the Law on the Eradication of Terrorism Crimes and to analyze the forms of bioterrorism crime attacks. The results of this study are First, the laws and regulations in Indonesia which regulate the crime of bioterrorism are still inadequate because they are not regulated in a limited manner. Bioterrorism crimes are still generally regulated and considered the same as the usual forms of terrorism, even though the forms of attacks and weapons used in bioterrorism crimes are very different. Second, there are several methods used by terrorists in sending biological agents which can be classified in the form of 1) The method of delivery by using aircraft or spray tanks. 2) The method of intentionally sending animals or plants that have been infected by a biological agent to spread disease in a desired target area; 3) Sending pathogenic biological agents directly through conventional delivery such as through PT. POS, JNE, JNT if in the context of Indonesia.